Demographic and Lifestyle Factors and Memory in European Older People - Steffl, Michal; Jandová, Tereza; Dadova, Klara; Holmerova, Iva; Vitulli, Piergiusto; Pierdomenico, Sante D; Pietrangelo, Tiziana (International journal of environmental research and public health, 2019)
OBJECTIVES: To investigate associations between demographic and lifestyle factors and memory performance in European people aged ≥60 years. METHODS: Data from 23,641 people with a mean age of 70.2 (95 % CI 70.1-70.3) were analyzed and drawn from the fourth wave of the Survey of Health, Ageing, and Retirement in Europe (SHARE). Generalized linear models were carried out to estimate the associations for both men and women. Memory performance was tested using two word-list learning tests with immediate and delayed recall in SHARE. RESULTS: age, severe limitations in physical activities, and any past alcohol problem were all negatively associated with memory performance. Contrarily, education level, higher nonalcoholic fluid intake, and engagement in sports activities more than once a week and in activities requiring a moderate level of energy were all positively associated with memory performance. Smoking showed a significant negative association only in the immediate recall test for both men and women together, whilst long-term illness showed association only in the delayed recall. Alcohol consumption was positively associated with memory performance in women, but in men, it depended on the drinking frequency. CONCLUSIONS: Demographic and lifestyle factors are associated with memory performance in the older population.
Keywords: Mental Recall; Humans; lidé středního věku; Alcohol Drinking; pití alkoholu; Female; Aged; senioři; lidé; Europe; rozpomínání; ženské pohlaví; Life Style; Male; životní styl; Middle Aged; Cross-Sectional Studies; mužské pohlaví; průřezové studie; Evropa